Facial pain associated with fibromyalgia can be marked by abnormal neuromuscular control: A cross-sectional study - Gui, Maísa Soares; Pedroni, Cristiane Rodrigues [UNESP]; Aquino, Luana M. Martins; Pimentel, Marcele Jardim; Alves, Marcelo Correa; Rossini, Sueli; Reimão, Rubens; Berzin, Fausto; Marques, Amélia Pasqual; Rizzatti-Barbosa, Célia Marisa (Oxford University Press (OUP), 2013)
Background. Temporomandibular disorder (TMD) development in fibromyalgia syndrome (FMS) is not yet fully understood, but altered neuromuscular control in FMS may play a role in triggering TMD. Objective. The purpose of this study was to verify the association between neuromuscular control and chronic facial pain in groups of patients with FMS and TMD. Design. A cross-sectional study was conducted. Methods. This study involved an analysis of facial pain and electromyographic activity of the masticatory muscles in patients with FMS (n=27) and TMD (n=28). All participants were evaluated according to Research Diagnostic Criteria for Temporomandibular Disorders and surface electromyography (SEMG). Myoelectric signal calculations were performed using the root mean square and median frequency of signals. Results. The data revealed premature interruption of masticatory muscle contraction in both patient groups, but a significant correlation also was found between higher median frequency values and increased facial pain. This correlation probably was related to FMS because it was not found in patients with TMD only. Facial pain and increased SEMG activity during mandibular rest also were positively correlated. Limitations. Temporal conclusions cannot be drawn from the study. Also, the study lacked a comparison group of patients with FMS without TMD as well as a control group of individuals who were healthy. Conclusions. Altered neuromuscular control in masticatory muscles may be correlated with perceived facial pain in patients with FMS. © 2013 American Physical Therapy Association.
Keywords: analysis of variance; cross-sectional study; electromyography; face pain; female; fibromyalgia; human; masticatory muscle; middle aged; pain assessment; pathophysiology; temporomandibular joint disorder; Analysis of Variance; Cross-Sectional Studies; Electromyography; Facial Pain; Female; Fibromyalgia; Humans; Masticatory Muscles; Middle Aged; Pain Measurement; Temporomandibular Joint Disorders